دراسة مخططات الاهتراء في منظومة عمل الفرامل - موسى المحمد; عدنان أحمد; بشار زيدان (Tishreen University, 2016)
الهدف الأساسي من صيانة وإصلاح المعدات والآليات أثناء فترة الاستثمار هو تخفيض كمية الأموال المصروفة من أجل المحافظة على صلاحية عملها في مختلف ظروف الاستثمار المحددة(نوعية مواد التصنيع، الطرق المستخدمة، درجات الحرارة، طبيعة الاستثمار،. .الخ). يمكن تحقيق هذا الهدف عندما نتحكم بتحولات الحالة الفنية للقطع الاحتكاكية للمعدات خلال فترة الاستثمار, ومعرفة القوانين الفيزيائية التي تتحكم بالانحرافات الفنية لها، لذلك قمنا بدراسة المخططات النظرية للاهتراء الجاف للفرامل لوسائل النقل انطلاقا من مخططات الاهتراء الرطب(الزيتي) للقطع الاحتكاكية في الآليات، ومن هذه المخططات قمنا بدراسة العلاقات الفيزيائية المحددة لكثافة الاهتراء وسرعته وتسارعه خلال فترة الاستثمار ومرحلة التشغيل غير الموثوق (غير الآمن)، مع الأخذ بعين الاعتبار الأساليب المتبعة في الصيانة التكنيكية الدورية وطرق القيادة ومتوسط مرات استخدام الفرامل و ...الخ. من خلال العلاقات التي حصلنا عليها، يمكننا التنبؤ ببدء مرحلة عدم فعالية الفرامل (البطائن الاحتكاكية) وتوقيت بدء مرحلة التشغيل الخطر(غير الموثوق)، الذي يعطينا مؤشراً للاستبدال أو المعالجة بالطرق الميكانيكية والكيميائية المعروفة. The main goal of maintaining and repairing equipment and machines during the investment stages is to reduce the amount of money spent in order to maintain the validity of their operation and the quality of their reliability under the different given investing conditions (type of manufacturing materials, methods used, temperatures, nature of investment, .... etc). This goal can be achieved if we are able to control changes in the technical conditions of equipment and the frictional parts during the investment stages, besides knowing the physical laws/rules that govern the technical changes properly. Therefore, we carried out a study on the theoretical plans of physical wear of brakes and the frictional parts in means of transportation. This is done starting from wet (oily) wear plans of the frictional parts in machines. Then, based on these plans we studied physical laws/rules determining the intensity of dry wear of brakes, along with its speed and acceleration during the investment and the unreliable, uneconomical (unsafe) operation stages, taking into consideration the methods used in periodical technical maintenance, ways of driving, and the average number of times brakes are used...etc . Based on these formulas obtained, we can estimate/predict the start of ineffectiveness of brakes and friction linings, in addition to the inception time of risky (unreliable) operation stage. Consequently, this stage gives us indications for replacement or treating with the traditional (known) mechanical and chemical ways, in light of the soaring prices of materials in the Syrian Arab Republic.